Tuberculosis en jornaleros migrantes indígenas en Sonora - Gerardo Álvarez Hernández; Patricia Aranda Gallegos; Maria del Carmen Candia Plata; Enrique Bolado Martínez; Luis Fernando López Soto; Jesús Adriana Soto Guzmán (Región y Sociedad, 2013)
Each year about 13,000 indigenous laborers migrate to work in the agricultural fields of Sonora, but little is known about their incidence of tuberculosis (tb) or how their perceptions and those of health personnel are related to the disease. Using tools from epidemiology and medical anthropology, we describe the epidemiological profile of tb during 2005-2010 in three agricultural fields in Sonora, and explore how social and cultural factors relate to tb occurrence. The incidence of tb in these communities is four times the national and state average. No ethnic group is documented in medical records, so tb may be underestimated in indigenous people. tb in this population exceeds the national rate, and there are gaps between the biomedical model and the belief systems of patients that reduce the effectiveness of disease control actions.